Pola Kepemimpinan Ketua Kwartir Daerah Kepanduan Hizbul Wathan Kota Yogyakarta Tahun 2017-2019 dalam Membentuk Kader Militansi Organisasi - Fandi Akhmad; Fadhlurrahman Fadhlurrahman (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Leadership in an organization is needed, because a leader has an effort to move people in this matter under him, in achieving certain goals that have been set, including in the leadership of Hizbul Wathan. After the emergence of the Hizbul Wathan Scouting Movement in 1960 which was signed by the Central Executive of Muhammadiyah at that time Buya Syafii Maarif made the cadres of the Muhammadiyah organization who had a guiding spirit rise and immediately spread in a structured diaspora to establish the Hizbul Wathan Scouting Movement in their respective regions, Yogyakarta was no exception. which became the forerunner to the center of the scouting movement of Hizbul Wathan. In the city Yogyakarta has also experienced ups and downs of the Hizbul Wathan scouting movement which has the slogan